Norepinephrine Dosage Is Associated With Lactate Clearance After Resuscitation in Patients With Septic Shock - Yu, Chao; Fan, Wenjing; Shao, Min (Frontiers in Medicine, 2021)
Background: Some septic shock patients have persistent hyperlactacidemia despite a normal systemic hemodynamics after resuscitation. Central venous oxygen saturation (ScvO2), mean arterial pressure (MAP) and central venous pressure (CVP) cannot be targets in subsequent hemodynamic treatments. Vasoplegia is considered to be one of the main causes of oxygen metabolism abnormalities in septic shock patients, and norepinephrine (NE) is the first-line vasopressor in septic shock treatment; its dosage represents the severity of vasoplegia. This study was performed to determine whether vasoplegia, as assessed by NE dosage, can indicate patients’ lactate clearance after the completion of resuscitation. Methods: A retrospective study was performed, and 106 patients with septic shock in an intensive care unit were analyzed. Laboratory values and hemodynamic variables were obtained upon completion of resuscitation (H0) and 6 h after (H6). Lactate clearance was deﬁned as the percent decrease in lactate from H0 to H6. Student’s t test, Mann‑Whitney U‑test, Chi-square or Fisher’s exact tests, logistic regression analysis, and receiver operating characteristic (ROC) curve analysis were performed for statistical analysis. Results: Patients with a mean age of 63.7±13.8 yrs, baseline APACHE II score of 21.0±5.1 and SOFA score of 12.7±2.7 were enrolled. The study found that after 6 h of resuscitation, lactate clearance (LC) was <10% in 33 patients (31.1%). Patients with six-hour LC<10% compared with 6-hour LC≥10% had a higher NE dose (μg·kg-1·min-1) (0.55 [0.36-0.84] vs 0.25 [0.18-0.41], p<0.001). Multivariate logistic regression analysis of statistically signiﬁcant univariate variables showed that NE dose had a signiﬁcant inverse relationship with 6-h LC<10%. The cutoff for NE was ≥0.32 μg·kg-1·min-1 for predicting 6-h lactate clearance after resuscitation, with a sensitivity of 75.76% and a specificity of 70.00%. Septic shock patients with an NE dose ≥0.32 μg·kg-1·min-1, relative to patients with an NE dose <0.32 μg·kg-1·min-1, had a greater 30-day mortality rate (69.8% vs 26.4% p<0.001). Conclusion: Some patients with septic shock had persistent oxygen metabolism disorders after hemodynamic resuscitation. NE dose may indicate vasoplegia and oxygen metabolism disorder. After resuscitation, septic shock patients with high-dose NE have lower lactate clearance and a greater 30-day mortality rate than those with low-dose NE.